Lacunary Interpolation by Spline function (0,3) Case - S., Rostam K.; H.J, Karwan (Sulaimani Journal for Pure and Applied Sciences, 2003)
The object of this paper is to obtain the existence, uniqueness and error bounds of quintic deficient splines interpolating the data (0,3).
Keywords: lacunary interpolation